Uwarunkowania wysokiej zależności pomiędzy budową ciała i wiekiem menarchy - Łaska-Mierzejewska, Teresa; Łuczak, Ewa (Polskie Towarzystwo Antropologiczne, 1996)
THE RELATIONSHIP BETWEEN THE BODY BUILD AND MENARCHEAL AGE. The groups of girls strongly differentiated by the economic situation of their families showed big differences in menarcheal age, but not in body build.
THE RELATIONSHIP BETWEEN THE BODY BUILD AND MENARCHEAL AGE